Governance and Tax Revenue in Asean Countries - Syadullah, Makmun (Journal of Social and Development Sciences, 2015)
Tax revenue is influenced by many factors. Existing studies reveal that political stability, level of corruption, quality of the policy, income per capita, share of agriculture to the GDP, and market openness are some of the factors influencing tax revenue. This study aims to analyze the influence of governance by using some indicators, such as political stability, government effectiveness, quality of regulation, law enforcement accountability and control on corruption in tax area through empirical analysis of ASEAN countries. Descriptive analysis and causality methods are employed in this study. causality method is used to determine the relationship between observed variables using panel regression. The results of the study indicate that the controlon corruption, voice and accountability and political stability variables have significant negative effects on the tax ratio, while rule of law and quality of regulatory variables have positive impact on the tax ratio.